Pengembangan Kewirausahaan Rumahan yang Ramah Lingkungan untuk Meningkatkan Perekonomian Komunitas Perempuan Single Parent di Desa Tetebatu Kecamatan Pallangga Gowa - Kifayah Amar; Syamsul Bahri; Mulyadi Hambali; Rosmalina Hanafi; Amrin Rapi; Sapta Asmal; Ilham Bakri; Farid Mardin; Muhammad Rusman; Saiful -; Irwan Setiawan; Syarifuddin M. Parenreng; Retnari Dian Mudiastuti; Nilda -; Nurfaidah Tahir; Nadzirah Ikasari; A. Besse Riyani Indah; Megasari Kurnia (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2022)
This community service program (PkM) focuses on empowering the single parent woman community in Tetebatu Village, Kec. Pallangga Kab. Gowa through socialization, training, and mentoring activities to improve skills in making environmentally friendly soap products. This PkM activity is carried out in collaboration between the Department of Industrial Engineering, Hasanuddin University and the Tetebatu Village Office, Pallanga District, Gowa Regency. The focus of this PkM is single parent women with the hope that they will be able to be economically independent through the business they run in the future. A total of 10 single parent women participated in the two-day activity which included introduction of environmentally friendly products, environmentally friendly soap-making production practices and discussions related to soap entrepreneurship opportunities and marketing strategies. During the implementation of this activity, pre-test and post-test were also conducted for participants as a way to measure the success of the activity. The results showed that participants' understanding of the definition of environmentally friendly increased by 80%. In addition, 90% of participants also understand the benefits of environmentally friendly products and about 60% of participants have understood the procedures, methods, and hygiene standards in making liquid soap after socialization and training.